Design and analysis of a first-order sigma-delta analog-to-digital converter for MEMS resistive sensor - Ma, Li Ya; Nordin, Anis Nurashikin; Khan, Sheroz; Alam, A. H. M. Zahirul; Islam, Md. Rafiqul; Al-Khateeb, Khalid A. Saeed (2010)
This paper details the design and analysis of a first-order sigma-delta analog-to-digital converter (Σ-Δ ADC) for the MEMS resistive sensors. The working principles of the MEMS resistive sensor and Σ-Δ ADC are outlined first. To verify the functionality of the first-order Σ-Δ modulator, MATLAB© is used to simulate its overall block diagram. Each block is then designed as a CMOS circuit using Cadence Silterra 0.13μm standard COMS process. Finally, the necessary properties (such as quantization error, resolution and signal to noise ratio) of this interface circuit for MEMS resistive sensors are analyzed. It is presented that when connected to MEMS resistive sensors, the usage of Σ-Δ ADC can greatly reduce the quantization error when compared to the conventional Nyquist rate analog to digital converter.